2006
DOI: 10.1007/s00417-005-0173-6
|View full text |Cite
|
Sign up to set email alerts
|

25-gauge, sutureless vitrectomy and standard 20-gauge pars plana vitrectomy in idiopathic epiretinal membrane surgery: a comparative pilot study

Abstract: The TSV system is a safe and efficient surgical technique for ERM surgery. Operating time is significantly reduced, minimizing surgery-induced trauma, and reducing postoperative intraocular inflammation and the patients' discomfort. The incidence of cataract formation may be less using TSV. Postoperative recovery is accelerated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
130
2
7

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 201 publications
(157 citation statements)
references
References 20 publications
13
130
2
7
Order By: Relevance
“…However, other studies have shown quicker visual recovery and fewer complications with small-gauge trans-conjunctival sutureless vitrectomy techniques for ERM removal. [14][15][16] One of the limitations of this study was the use of VA as the sole measure of surgical success. Metamorphopsia is also a significant contributor to morbidity in patients with ERMs and it has been shown that, even though VA alone may not improve following ERM removal, metamorphopsia and quality of life does.…”
Section: Discussionmentioning
confidence: 98%
“…However, other studies have shown quicker visual recovery and fewer complications with small-gauge trans-conjunctival sutureless vitrectomy techniques for ERM removal. [14][15][16] One of the limitations of this study was the use of VA as the sole measure of surgical success. Metamorphopsia is also a significant contributor to morbidity in patients with ERMs and it has been shown that, even though VA alone may not improve following ERM removal, metamorphopsia and quality of life does.…”
Section: Discussionmentioning
confidence: 98%
“…[3][4][5][6][7][8][9][10][11][12] Furthermore, a few recent reports continue to prove the superiority of MIVS in direct comparison with conventional 20-gauge vitrectomy. 6,7,[14][15][16][17] Although the makers of each of two commercially available small gauges, 25 and 23 gauges, claim to offer the safest and best product, no studies have yet compared the 25-and 23-guage systems.…”
Section: Discussionmentioning
confidence: 99%
“…MIVS shortens operative time and facilitates postoperative recovery. [4][5][6][7][8][9][10][11][12] This 25-gauge sutureless system, however, was useful only in cases of relatively simple vitreoretinal pathology owing to limitations in cutter performance and a lack of necessary accessory instruments. In 2005, Eckardt developed 23-gauge sutureless vitrectomy using an obliquely entering trocar cannular system.…”
Section: Introductionmentioning
confidence: 99%
“…Pars plana vitrektomi (PPV) ilk kez 1971 y›l›nda Machemer taraf›ndan uygulanm›flt›r (1) 25-G TSV'nin epiretinal membran ve makula deli¤i gibi vitreomaküler yüzey hastal›klar›, vitreus hemorajisi, proliferatif vitreoretinopatiyle komplike olmayan retina dekolman› ve yayg›n vitreus diseksiyonu gerektirmeyen traksiyonel diyabetik retina dekolman›nda uygulanabilece¤i bildirilmifltir (6)(7)(8)(9)(10). Biz de çal›flmam›zda, idiyopatik makula deli¤i tedavisinde 25-G TSV'nin etkinli¤ini ve güvenilirli¤i-ni araflt›rd›k.…”
Section: Giriflunclassified
“…Ayr›ca kullan›lan mikrokanül sistemi, enstrümanlar›n göz içine tekrarlayan girifllerinin neden olaca¤› hasara karfl› girifl yerini korur. küçük olmas› nedeniyle, retina fototoksik etkiye daha az maruz kal›r (10,14). ‹diyopatik makula deli¤i tedavisinde 25-G TSV, ILM soyulmas› ve intraoküler CF38 gaz tamponad› uygulanan 84 gözün incelendi¤i bir çal›flmada, makula deli¤i kapanma oran› %93 olarak bildirilmifltir.…”
Section: Tart›flmaunclassified